METHODS OF SPECTRAL ANALYSIS OF RANDOM PROCESS FLUCTUATIONS OF VOLTAGE AND CURRENT FEEDER TRACTION SUBSTATION DC - Petrov, A. V. (Science and Transport Progress, 2010)
The methods for determination of spectral composition of random functions of voltage and current of traction substation feeder are proposed. The low frequency components of their spectra (interharmonics) are obtained.